Role of Enterovirus ECHO 30 as the etiological agent of enterovirus infection in the North-West of Russia in 2013 - M. A. Bichurina; N. I. Romanenkova; L. N. Golitsyna; N. R. Rozaeva; O. I. Kanaeva; S. G. Fomina; T. I. Krainova; L. A. Shishko; T. A. Gordienko; V. A. Pianykh; T. G. Ivanova; S. N. Smelkov; et al. (IPO “АIDSSPbR", 2014)
In 2013 after two previous years when the situation had been calm the incidence rates of enterovirus infection significantly increased on certain territories of the North-West of Russia. In Novgorod and Vologda regions and in Saint-Petersburg enterovirus meningitis group cases were registered. The etiology of enterovirus infection was studied by virological and molecular methods. Enterovirus ECHO30 was identified as the principal etiological agent of the cases. Molecular study revealed that enteroviruses ECHO30 isolated in the North-West of Russia belonged to the genotype H and formed two subtypes inside this genotype. Phylogenetic analysis has shown that enteroviruses ECHO30 of both subtypes were closely related to the strains detected in different provinces of China in 2010-2013. Probably enteroviruses ECHO30 of the genotype H which largely circulated in Russia in 2013 and practically had not been detected in the country earlier had been imported on the territory of Russia from South-East Asia. Enteroviruses ECHO30 isolated in Arkhangelsk and Novgorod regions in 2008-2009 belonged to another genotype Ec2. Enteroviruses of this genotype had circulated at that time in the European countries. В 2013 г. после относительно спокойной ситуации в течение двух предыдущих лет заболеваемость энтеровирусной инфекцией на ряде территорий Северо-Западного федерального округа резко возросла. Были зарегистрированы групповые заболевания энтеровирусным менингитом в Новгородской, Вологодской областях и в Санкт-Петербурге. Проведена расшифровка этиологии заболеваний энтеровирусной инфекцией с использованием вирусологического и молекулярно- генетического методов исследования. В качестве основного этиологического агента был идентифицирован энтеровирус ЕСНО 30. Установлено, что изолированные на Северо-Западе России вирусы ЕСНО 30 относились к генотипу Н и сформировали две филогенетические группы. Филогенетический анализ показал, что энтеровирусы ЕСНО 30 обоих субтипов были наиболее близко родственны штаммам, выделенным в разных ...